Tinjauan Sistem Informasi Akuntansi Persediaan Barang Dagang Pada PT DAYA HIDUP SEMESTA - Gunawan, Ilham Bintang; Effendy, Marwan; Triandi, Triandi (Program Vokasi dan LPPM IBI Kesatuan, 2024)
PT Daya Hidup Semesta is a trade company whose main activity is to buy, store as stock and sell health and safety products under the 4Life brand. The supply of goods is a very important factor for a trading company because the main activity of the trading company is to sell the supply of Goods to the customer in his business to make a profit or profit. Therefore, the supervision of the management of goods and services should be carried out in accordance with the procedures of registration, the procedure of demand and the procedure for the production of the goods have been applied according to the theory of which there has been adequate separation of tasks, the process of authorization of documents and the system of recording of the application of computerized supplies and there is internal verification independently. Keywords: accounting system, and merchandise supplies